Clear subretinal fluid in a case of non-neovascular early-onset drusen: Swept-source imaging evaluation. Issue 1 (January 2022) - Agarwal, Aniruddha; Handa, Sabia; Querques, Giuseppe; Gupta, Vishali
A 50-year-old male presented with recent metamorphopsia in the right eye. Fundus examination revealed bilateral multiple cuticular drusen along with few large colloid drusen (phenotype 3 cuticular drusen). No vitelliform material was evident in the macula in either eye. Fluorescein angiography (FA), indocyanine green angiography (ICGA) did not demonstrate a macular neovascularization (MNV) in either eye. Swept-source optical coherence tomography (SS-OCT) revealed sub-retinal pigment epithelial (RPE) drusen and a clear space beneath the inter-digitation zone and above the RPE-Bruch's complex. SS-OCTA did not reveal MNV in either eye. The patient was kept under observation, and follow-up at 3 months did not reveal any structural change. Among patients with early-onset drusen, vitelliform detachments may occur due to accumulation of yellow pseudo-vitelliform material. However, serous detachments with an "optically clear" subretinal space can occur by the same mechanism without MNV. Such patients do not merit therapy with anti-vascular endothelial growth factor agents.